Pharmacokinetics of paracetamol in chicks treated with metronidazole - S.M. Hussain (Iraqi Journal of Veterinary Sciences, 2017)
Effect of metronidazole on the pharmacokinetics of paracetamol were examined in chicks. Chicks were dosed orally with metronidazole at 350 mgkg of body weight daily (10 -13 days of age). On the last day of metronidazole dosing, chicks injected intraperitoneally with paracetamol at of 50 mgkg of body weight. Paracetamol appeared in chick plasma at 52.00, 45.00, 40.75, 32.75, 23.25 µg ml after 0.25, 0.50, 0.75, 1, 2, 4 hours of injection respectively. A significantly decreased the concentration paracetamol at times of 0.25, 0.50, 0.75, 1, 4 hours post injection and appeared at concentrations of 36.62, 35.37, 25.62, 20.50, 11.00 µgml. These was reflected by changes in the pharmacokinetics of paracetamol as show by the increase elimination rate constant (48%) and decrease in the half-life (32 %) and increase in volume distribution (29%) and increase in clearance by (96%) and decrease in the area under the plasma curve (33%) and decrease in the area under moment curve 65% and lack mean residence time (33%). These results indicate that oral dosing of chicks with metronidazole for four consecutive days and this effect increase in the elemination rate of paracetamol and this effect must be considered when therapy with paracetamol when given during metronidazole therapy.